Chemical composition, total polyphenols, antioxidant and cytotoxic activity of Vitex gardneriana Schauer's ethanolic fruit extract (Research, Society and Development, 2022)
The present work evaluated the phytochemical composition and the antioxidant and cytotoxic activities of the ethanolic extract of the fruit of Vitex gardneriana Schauer. Thus, to meet the objectives proposed in the present work, phytochemical tests were carried out to detect the presence of secondary metabolites, through qualitative tests with the formation of precipitates, detection and identification of compounds performed by High Performance Liquid Chromatography, and quantification of total polyphenols using the Folin-Ciocalteu reagent. The antioxidant assay was performed by determining the capture of free radicals (DPPH), and for the toxicity test performed, the bioassay with Artemia Salina was used. As for the phytochemical tests, they revealed the presence of alkaloids, saponins, tannins, chlorogenic acid and total polyphenols. For the antioxidant assay, the fruit extract showed a DPPH radical scavenging capacity between concentrations of 500 to 3.9 μg mL-1. Regarding the toxicity test, the material tested did not show cytotoxic action on Artemias salina. Thus, it is possible to conclude that the ethanol extract has antioxidant action, due to the presence of its chemical constituents.